Marketing Politik Partai Gerindra dalam Pemilihan Legislatif 2019 di Kabupaten Gresik - Ainul Yaqin Tirta Saputra (Jurnal Indonesia Sosial Sains, 2021)
This study examines the political marketing strategy undertaken by DPC Gerindra Party Gresik in 2019 legislative elections at Gresik. Political Marketing conducted by Gerindra party concentrated on powerful figures in Gresik, also Gerindra party were utilizing Prabowo Subianto who at the time was also a candidate for President. The research question that arises is what kind of political marketing strategy implemented by Gerindra party. To answer the question, this study used qualitative research methods. The research subject is the Chairman of DPC Gerindra Party Gresik, Bapilu Chairman DPC Gerindra Party Gresik, legislative candidates who are members of the board with the acquisition of the highest vote in the party, and the legislative candidate’s campaign team. Results of this study are the party Gerindra implemented politics marketing strategies with figures reinforcement variable and utilize Prabowo Subianto figure who becomes a candidate for President to be able to reap high vote result so that the party Gerindra could ranks 3rd biggest in Gresik and in addition to a fairly high vote result, Gerindra party could deliver its 8 candidates to become members of DPRD Gresik where the 2009 legislative elections the party Gerindra could only able to deliver 1 legislative candidates to became members in DPRD Gresik.